“If you weren’t my friend I wouldn’t know who I was”: Care Virtues and the Relational Self in Sally Rooney’s Beautiful World, Where Are You - Carregal-Romero, José (International Journal of English Studies, 2024)
Set in contemporary Ireland, Sally Rooney’s Beautiful World, Where Are You (2021) focuses on the relationship dynamics between characters who struggle with intimacy and human connection, against the backdrop of the individualist ethos and existential anxieties induced by current neoliberal systems. Drawing on care ethics, vulnerability and relationality theory, this analysis of Beautiful World underscores how Rooney constructs her characters’ psychological evolution through their progressive, albeit irregular, adoption of care virtues within relationships. The analysis shall apply Khader’s taxonomy of care virtues (2011), which include “loving attention” –a willingness to appreciate and accommodate the particular nature of the other–, “the transparent self” –an awareness of how our self-interests block our recognition of the other’s needs–, and “narrative understanding”, a desire to engage with the other’s personal history so as to make decisions that promote his/her well-being.